O outro lado da saúde: abrace seu bairro - Gellerth, Cassia Maria (2012)
The herein mastership dissertation work intends to disclose and analyze the practice of Social Service in the Project Embrace your District - Projeto Abrace seu Bairro of the Welfare Society of the Syrian Lebanese Hospital - Hospital Sírio Libanês, SBSHSL, in charge of the actions for Health Promotion addressed to families of the Bela Vista District in the city of São Paulo, who are also taken care of by the Social Pediatrics Department of the referred institution. This is about a theoretical-practical analysis of the intervention of social service for this population. We have identified that social assistance, education and family perform activities articulated in a network in the territory inter-sectoriality, through social and public policies conquered since the Citizen Chart, of 1988. From this angle, the following were selected as social subjects. Families taken care by Abrace: family 1, up to one year of care; family 2, up to 5 years of care and family 3, taken care of for tem years, that is, since the Project was started. The criterion drawn up was the adhesion and permanence of these families within the project, the differences and specificities for the inclusion in the care, as well as the verification of the limits and possibilities of each one, to take part in the interviews, for these were made in domiciliary social visits. The methodological way chosen for the analysis and revelation of the study object is the case study, as a particular form of qualitative investigation which attempted to understand, from the perspective of these subjects who participate in the Project day by day, their comprehensions and meanings on this intervention, through semi structured interviews with a script. Suggestions are presented to put into practice an inter-sectorial and inter disciplinary public policy which must have centrality in the relationships among the public, the private and the organized civil society. Thus, it was understood that this population´s human needs will be made effective as a right in their integrality, in the daily exercise of conscious participation for the construction of an organized civil society, inclusive and intended for citizenship